Hypertrophic Cardiomyopathy Phenotypes and the Utility of Cardiac Magnetic Resonance Imaging: An Illustrative Case Series - Grace Alexander; Mahi L. Ashwath (Annals of Internal Medicine: Clinical Cases)
Cardiac magnetic resonance imaging is the most sensitive and specific imaging method for characterizing the myocardium, monitoring disease, and risk stratifying many cardiomyopathy phenotypes. We present 3 cases of cardiomyopathy with hypertrophic phenotypes which demonstrate the advantages of cardiac magnetic resonance imaging. Ultimately, when investigating cardiomyopathies with a hypertrophic phenotype, a systemic evaluation using a “cardiomyopathy mindset” is needed, and multimodality imaging is a key piece of this process.